ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PESERTA DIDIK DALAM PEMILIHAN SEKOLAH LANJUTAN TINGKAT ATAS (SLTA) - Ida Putri Lestari; Ahmad Yusuf Sobri; Desi Eri Kusumaningrum (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2019)
Abstract: The purpose of this study was to know (1) what are the factors the influence students in the selection of high school in Blitar City, (2) the high level of factors that effects students in the selection of high school in Blitar City, (3) the dominant factors affecting participant students in the selection of high school in Blitar City. This research uses a quantitative approach and is include in the type of descriptive research with exploratory analysis technique. The total population in this study was 3722. Determination of the sample using the Random Sampling technique with calculations using the Slovin Formula as many as 361 respondents, with a 5% error chance. Data collection tools use a questionnaire in the form of a positive statement with the assessment using a Likert Scale on each item statement. The results showed factors that influence students in selecting schools, namely: facility factors (16.60%), human resource factors (HR) (10.98%), and superior school factors (9.66%). This study was able to explain 37.25% of students’ factors in choosing schools, due to the limitations of the factors in this study so that 62.75% could not be explained such as school location factors, tuition fees, extracurricular activities, and education quality.Key Words: analysis factors, choosing school, leaners Abstrak: Tujuan penelitian ini mengetahui (1) faktor yang mempengaruhi peserta didik dalam pemilihan SLTA Negeri di Kota Blitar, (2) tingginya tingkat faktor yang mempengaruhi peserta didik dalam pemilihan SLTA Negeri di Kota Blitar, (3) faktor dominan yang mempengaruhi peserta didik dalam pemilihan SLTA Negeri di Kota Blitar. Penelitian ini menggunakan pendekatan kuantitatif dan termasuk dalam jenis penelitian deskriptif dengan teknik analisis eksploratori. Jumlah populasi pada penelitian ini sebanyak 3722 responden. Penentuan sampel menggunakan teknik Random Sampling dengan perhitungan menggunakan Rumus Slovin yaitu sebanyak 361 responden, dengan peluang eror 5%. Alat pengumpulan data menggunakan angket dalam bentuk  pernyataan positif dengan penilaian menggunakan Skala Likert pada setiap butir pernyataan. Hasil penelitian menunjukkan faktor yang mempengaruhi peserta didik dalam memilih sekolah, yaitu: faktor sarana (16.60%), faktor sumber daya manusia (SDM) (10.98%), dan faktor sekolah unggul (9.66%). Penelitian ini mampu menjelaskan 37.25% faktor peserta didik dalam memilih sekolah, karena keterbatasan faktor pada penelitian ini sehingga 62.75% belum bisa dijelaskan seperti faktor lokasi sekolah, biaya pendidikan, ekstrakurikuler, dan mutu pendidikan.Kata Kunci: analisis faktor, memilih sekolah, peserta didik